Physical and culinary analysis of long gluten-free extruded pasta based on high protein quinoa flour - Córdoba-Cerón, Deiny Maryeli; Carranza-Saavedra, Darwin; Roa-Acosta, Diego Fernando; Hoyos-Concha, Jose Luis; Solanilla-Duque, Jose Fernando (Frontiers in Sustainable Food Systems, 2022)
The consumption of foods with high protein content from pseudocereals is of great industrial interest. Pasta has a high gluten content; consequently, obtaining these gluten-free products is a technological challenge. The products obtained from quinoa show excellent results in protein and fiber with low glycemic index. This work focused on studying the effect of quinoa fat on the production of long pasta by extrusion in different mixtures of hyperprotein quinoa (HHP). It was observed that formulations with high percentages of starch showed a higher expansion rate, due to a higher fat content. Likewise, extruded pastes showed higher values of brightness than those containing lower percentages of starch and crude fat. The fracturability results were associated with the resistance of the paste to the pressure exerted for its deformation, which does not exceed 3.73 mm. The formulations with lower fat content presented high values in fracture stress due to the low diffusion of water and lipids. It was shown that fat has an indirect influence with a strong correlation with the expansion index and fracture stress and a moderate correlation (p > 0.05) with Young's modulus, indicating that increasing the added fat content increases the percentage of mass loss by baking. The melting and cohesiveness of all components improved during extrusion due to the pregelatinization of cassava starch, the addition of defatted HHP and the availability of quinoa starch granules.